AUDIT SISTEM INFORMASI APLIKASI PERSEDIAAN PADA PT SS - Evy Herawati (Bina Nusantara University, 2008)
The research objective was to evaluate and determine how far the application of information system inventories that are running (including management controls and application controls) have been able to provide reliable information and where time and reduce risk to an acceptable level by the company also provides recommendations for companies in order to minimize the risk that existed at the moment. The research method used “around the computer” is testing and evaluating audit through management control, in performing input and output controls for application systems based on the quality of input supply and output that will produce a report. The results of this study was to determine the inventory of information system applications that use the SS company can provide adequate and reliable information and timely, thus simplifying the management to make sound decisions related to inventory policy.Keywords: audit, information systems inventory, control, corporate